2006
DOI: 10.1007/s10775-006-9107-z
|View full text |Cite
|
Sign up to set email alerts
|

Students’ career concerns: challenges facing guidance providers in higher education

Abstract: The study reported here examined higher education career guidance at the University of Jyvä skylä in Finland. In a survey (N = 880), students were asked to describe how much thinking they had done about their future career and forthcoming transition from university to working life. The use of different sources of guidance and counselling service providers was examined from the perspective of a student-centred holistic model of guidance. On the basis of the empirical findings, challenges facing career guidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
2
10
0
4
Order By: Relevance
“…However, these numbers are lower than those reported by Warbah et al (2006) who reported that 21% of their sample faced some kind of psychological problems. In addition, the reported types of concerns stated above are consistent with previous research that indicates that students' highest ranked needs are in the social, personal, academic and career areas, both in Greece (i.e., Papadioti and Damigos 2003) and internationally (i.e., Bradley 2000;Güneri et al 2003;Lairio and Penttinen 2006). Significant gender differences were observed with regard to the participation of young men and women in the four problem groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, these numbers are lower than those reported by Warbah et al (2006) who reported that 21% of their sample faced some kind of psychological problems. In addition, the reported types of concerns stated above are consistent with previous research that indicates that students' highest ranked needs are in the social, personal, academic and career areas, both in Greece (i.e., Papadioti and Damigos 2003) and internationally (i.e., Bradley 2000;Güneri et al 2003;Lairio and Penttinen 2006). Significant gender differences were observed with regard to the participation of young men and women in the four problem groups.…”
Section: Discussionsupporting
confidence: 87%
“…The great majority of graduates experience uncertainty upon graduation as they question the role of education for employability (Lairio and Penttinen 2006). For overcoming such uncertainty and negotiating labour market barriers, careers research highlights the role of CSM.…”
Section: Graduate Employability As Processmentioning
confidence: 99%
“…At the university, students build an academic identity and a work identity (Johansson, Kopciwicz, and Dahlgren 2008, 220;Archer 2008, 401;Pratt, Rockmann, and Kaufmann 2006, 256). Research at the University of Jyväskylä (Lairio and Penttinen 2006) indicated that over 90% of the students surveyed had a large number of career-related questions in the final stages of their studies and over 70% of the respondents reported career concerns at the very outset of their studies. Students' career concerns were divided into three categories of deliberating about the future.…”
Section: Work-related Questions Within Students' Study Paths and Visimentioning
confidence: 99%